Descriptive set theory - Moschovakis, Yiannis N. (Studies in logic and the foundations of mathematics, 1980)
Now available in paperback, this monograph is a self-contained exposition of the main results and methods of descriptive set theory. It develops all the necessary background material from logic and recursion theory, and treats both classical descriptive set theory and the effective theory developed by logicians.